Simultaneous 12-lead QRS detection by K-means clustering algorithm - Nagal, Devendra; Sharma, Swati (International Conference on Recent Advances and Innovations in Engineering (ICRAIE-2014), 2014)
An electrocardiogram (ECG) is a recording of the electrical activity of the heart. Analysis of ECG data can give important information about the health and condition of the heart and can help physicians to diagnose cardiac arrhythmias, acute myocardial infarctions, conduction abnormalities, and many other heart diseases. ECGs can also be used to determine heart rate by calculating the time between successive QRS complexes. This paper presents an application of K-means algorithm applied on 25 subjects of CSE data set-3 for the detection of QRS complexes in the simultaneously recorded 12 lead ECG. The detection rate of 99.89% is achieved.